Physiological quality and expression of genes in seeds of Handroanthus serratifolius subjected to drying - Leandra Helena do Nascimento Gonçalves; Heloísa Oliveira dos Santos; Édila Vilela de Resende Von Pinho; Thaís de Andrade; Iolanda Vilela Von Pinho; Rucyan Walace Pereira (Journal of Seed Science, 2015)
Handroanthus serratifolius seeds are considered orthodox and have some mechanisms that assist in desiccation tolerance, like heat-resistant proteins and the presence of protective systems against free radical production. In order to investigate the drying effect on the quality of Handroanthus serratifolius seeds collected with 28% water content two methods were used: slow drying (30 °C) and fast drying (45 °C) until water contents equaled 20%, 15%, 10% and 5%. Seed quality was assessed by germination test, first count of germination, speed germination, emergence and speed emergence. The expression of heat-resistant proteins and enzymes catalase, esterase and isocitrate lyase was assessed by electrophoresis. The gene expression of sHSP17.5, CAT3 and ICL6 was quantified by real time PCR. Higher values of germination and vigor were obtained in seeds with 20% water content, subjected to fast drying. There was induction of heat-resistant proteins expression for both drying methods. There was variation in the electrophoretic pattern of catalase, esterase and isocitrate lyase in seeds subjected to different treatments. The gene expression in Handroanthus serratifolius seeds varies depending on methods of drying and water content of seeds. The drying of Handroanthus serratifolius seeds until the water content between 15 and 10% compromises their physiological quality.